2021
DOI: 10.1038/s41598-021-95159-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of some evolutionary-based models in optimization of dam reservoirs operation

Abstract: Deriving optimal operation policies for multi-reservoir systems is a complex engineering problem. It is necessary to employ a reliable technique to efficiently solving such complex problems. In this study, five recently-introduced robust evolutionary algorithms (EAs) of Harris hawks optimization algorithm (HHO), seagull optimization algorithm (SOA), sooty tern optimization algorithm (STOA), tunicate swarm algorithm (TSA) and moth swarm algorithm (MSA) were employed, for the first time, to optimal operation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The position of each particle is corrected by taking small movements in the neighborhood of the global optimum. By adopting the correct sequence of these two phases, it is possible to lead particles towards the global optimum 37 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The position of each particle is corrected by taking small movements in the neighborhood of the global optimum. By adopting the correct sequence of these two phases, it is possible to lead particles towards the global optimum 37 .…”
Section: Methodsmentioning
confidence: 99%
“…A new generation is formed by selecting some parents and some offspring according to their fitness values, and by rejecting others to keep the population size constant. After the predetermined number of generations is performed, the algorithm converges to the best chromosome, which hopefully represents the optimal solution or may be a near-optimal solution of the problem 37 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, dam reservoirs play a very important role in current civilizations, hence their operation needs to be managed effectively. Policies for reservoir dam operation are generally determined in order to set the course towards achieving desired objectives such as the maximization of hydropower generation; and the minimization of operation costs, risks, and deficiencies particularly in terms of water release and storage (Asadieh and Afshar 2019;Ehteram et al 2018;Motlagh et al 2021;Sharifi et al 2021). As there are often various different objectives in dam reservoir operations, optimization is required to search for optimum solutions that simultaneously maximizes benefits on all fronts, given a set of objective functions and constraints (Chong et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, limited studies have also been found on the usage of HHO in dam reservoir operation optimization. Sharifi et al (2021) compared the performance of several evolutionary-based models, namely HHO, MSA, GA, PSO, seagull optimization algorithm (SOA), sooty tern optimization algorithm (STOA), and tunicate swarm algorithm (TSA), in optimizing the operation of the Halilrood multi-reservoir system. It was found that HHO was among the top performing models in the study in terms of objective value function, CPU run-time, and convergence rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation